Kemampuan Koneksi Matematis Siswa Berdasarkan Literasi Numerasi dalam Meyelesaikan Masalah Aljabar - Upara, Nursafa; Gelora Mastuti, Ajeng; Juhaeivah, Fahruh (Journal of Mathematics Learning Innovation, 2024)
Mathematical connection skills are important because they support students to understand a concept substantially and help them to increase their understanding of other disciplines through the connection between mathematical concepts and concepts from other disciplines. The aim of this research is to determine students' mathematical connection abilities based on numeracy literacy in solving algebra problems. The method used in this research is descriptive qualitative. The subjects in this study were 3 people who met the indicators of mathematical connection ability, consisting of one person with low ability, one person with medium ability, and one person with high ability. The instruments used were an interview guide and a mathematical connection ability test. The results of the research show that students with high ability meet all indicators of mathematical connection, students with moderate ability meet several indicators of mathematical ability, and students with low ability do not meet all indicators of mathematical connection ability. It is hoped that the results of this research will provide a better understanding of students' mathematical connection abilities in solving algebra problems. With a better understanding of the importance of mathematical connections in substantially understanding mathematical concepts, it is hoped that it can encourage the development of learning strategies that can improve students' mathematical connection abilities at school. It is also hoped that the results of this research can make a positive contribution in efforts to improve students' understanding and mathematical skills.